Extraction and spray-drying of anthocyanin from seeds of two species of Kundang, Bouea macrophylla Griffith and B. oppositifolia (Roxb.) Adelb - Ibrahim, Nur Hafezah (2019)
Anthocyanin gain attention recently due to its potential health benefits and as an alternative source to synthetic colourants. Pinkish-purple seed of Kundang (Bouea macrophylla) can be a good source of natural colourant. Since information on the extraction of anthocyanin from Kundang seeds is scarce, therefore the objectives of this research were (i) to evaluate the effects of different solvents on the extraction of anthocyanin from Kundang seeds and (ii) to optimise spray-drying condition of B. macrophylla seeds extract. In the first part of this study, five different solvents [distilled water, absolute ethanol, aqueous ethanol (70%), acidified aqueous ethanol with acetic acid (pH 1), and acidified aqueous ethanol with hydrochloric acid (pH 1)] were used to extract anthocyanin from two different species of Kundang (Bouea macrophylla and Bouea oppositifolia) to explore its potential as natural colourant with anthocyanin and antioxidant properties. Proximate compositions of the Kundang seeds were identified prior to the extraction, where the moisture, fat, protein, ash, and carbohydrate content were in the ranged of 9.82-14.87%, 0.67-1.15%, 5.13-5.74%, 1.19-1.50%, and 77.82-82.10%, respectively. The results obtained indicated that type of solvents used tend to influence the extractability of anthocyanin and antioxidant compounds of the Kundang seeds. However, acidified solvents, regardless of the acid type, showed the most prominent results for both species of Kundang. For B. macrophylla seeds, aqueous ethanol with HCl produced extract with the highest extraction yield (17.5%), a (66.30) and b (17.51) values, total monomeric anthocyanin (TMA, 1.2 mg cyanidin-3-O-glucoside/g extract), total flavonoid content (TFC, 6.58 mg RE/g extract), and DPPH scavenging activity (82.22%) compared to other solvents (p<0.05). Besides, the B. macrophylla seeds contained cyanidin-3-O-glucoside, malvidin-3-O-glucoside, and peonidin-3-O-glucoside. This finding could provide insight into B. macrophylla seeds as a novel source of natural anthocyanin food colourants with antioxidant benefits. Since anthocyanins are unstable during processing, the study on spray-drying of B. macrophylla seeds extract was conducted and the sensory evaluation acceptability of ‘agar-agar’ with the spray-dried seeds extract powder was determined in the second part of this study. The central composite design (CCD) of the response surface methodology (RSM) was performed to optimise the spray-drying of B. macrophylla seeds extract and to analyse the effect of inlet air temperature (160-180 °C) and maltodextrin (DE10) concentration (3-17%, w/w) on the powder characteristics. Significant response surface models with high coefficients values (R2>0.910) for the solubility (0.979) was obtained from the experimental data. Sensory analysis on the acceptability of ‘agar-agar’ that contained spray-dried powder obtained at 170 °C of the inlet air temperature and maltodextrin (DE10) concentration at 10% (w/w) was carried out by 30 untrained panellists. A non-significant difference (p>0.05) was observed in terms of the overall aroma, texture, flavour, and acceptability except for the overall colour, whereby commercial colouring powder (CCP) had higher acceptance in colour compared to spray-dried B. macrophylla seeds extract powder (SSP, p<0.05). As the conclusion, B. macrophylla seeds extract powder potent to be a substitute to the synthetic food colouring.